Radical trust : - Healey, Joe (John Wiley & Sons, 2007)
Healey brings to the forefront the importance of trust to business effectiveness in a new and fresh way. It takes the alignment of 'what we do,' 'what we say,' and 'who we are' to build trust with others. Business relationships founded on trust may be the single biggest employee retention tool available. Healey shows us how to build those kinds of relationships. Any leader would benefit from the insights he shares in Radical Trust.